2014
DOI: 10.1128/jvi.02296-13
|View full text |Cite
|
Sign up to set email alerts
|

The Viral E8^E2C Repressor Limits Productive Replication of Human Papillomavirus 16

Abstract: Productive replication of human papillomavirus type 16 (HPV16) occurs only in differentiated keratinocyte cells. In addition to the viral E2 activator protein, HPV16 and related HPV types express transcripts coding for an E8^E2C fusion protein, which limits genome replication in undifferentiated keratinocytes. To address E8^E2C's role in productive replication of HPV16, stable keratinocyte cell lines containing wild-type (wt), E8^E2C knockout (E8؊), or E8 KWK mutant (mt) genomes, in which conserved E8 residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 48 publications
8
96
0
Order By: Relevance
“…We also investigated the effects of IFN-␤ on HPV16 transcription. Three different stable human keratinocyte cell lines that maintain extrachromosomal genomes (24,25) were treated with IFN-␤ (1,000 U/ml) for 6 h, and then E2 and E7 transcripts were analyzed by qPCR. Depending on the cell line, HPV16 transcripts were reduced to 60 to 80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the effects of IFN-␤ on HPV16 transcription. Three different stable human keratinocyte cell lines that maintain extrachromosomal genomes (24,25) were treated with IFN-␤ (1,000 U/ml) for 6 h, and then E2 and E7 transcripts were analyzed by qPCR. Depending on the cell line, HPV16 transcripts were reduced to 60 to 80% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HPV16 wild-type-positive cell lines have been previously described (24,25). The LKP1 and the CIN1 lesion-derived CIN612-9E cell lines contain replicating HPV31 genomes and have been described before (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…The major HR-HPV, HPV16, -18, and -31, express a spliced mRNA that links the E8 gene to the E2 gene and has the capability to encode an E8^E2C (or E8/E2 or E8^E2) protein (7)(8)(9)(10). Genetic analyses have revealed that E8^E2C inhibits genome replication of HR-HPV16, -18, and -31 in undifferentiated cells, and there is also evidence that E8^E2C limits productive replication of HPV16 in differentiated cells (8)(9)(10)(11). The HPV16, -18, and -31 E8^E2C proteins bind to the viral origin of replication and are potent repressors of transcription and the E1/ E2-dependent replication (7,9,(11)(12)(13)(14).…”
Section: Hpv16 Replicates In Differentiating Epithelia and Can Cause mentioning
confidence: 99%
“…Genetic analyses have revealed that E8^E2C inhibits genome replication of HR-HPV16, -18, and -31 in undifferentiated cells, and there is also evidence that E8^E2C limits productive replication of HPV16 in differentiated cells (8)(9)(10)(11). The HPV16, -18, and -31 E8^E2C proteins bind to the viral origin of replication and are potent repressors of transcription and the E1/ E2-dependent replication (7,9,(11)(12)(13)(14). Both activities require the conserved E8 part, which recruits cellular corepressor molecules (14)(15)(16).…”
Section: Hpv16 Replicates In Differentiating Epithelia and Can Cause mentioning
confidence: 99%
See 1 more Smart Citation